Promoção de crescimento em milho pela inoculação e coinoculação de Azospirillum, Bacillus E Pseudomonas - Silva, André Silas Lima (2022)
The inoculation and co-inoculation of plant growth promoting bacteria (BPCV) contributed to the greater growth, development and productivity of the corn crop. Thus, the present study aimed to evaluate inoculation and co-inoculation responses of Azospirillum brasilense, Bacillus megaterium, B. subtilis, B. licheniformis and Pseudomonas fluorescens, in maize. For the study, two experiments were carried out under field conditions, in different location (municipalities of Braganey-PR and Entre Rios do Oeste-PR) with a randomized block design, with 12 treatments and four replications. The treatments were: T1-Control (no inoculation); T2 - Azospirillum brasilense; T3 - Bacillus megaterium e Bacillus subtilis; T4 - Pseudomonas fluorescens ; T5 - Bacillus licheniformis; T6 - A. brasilense + B. megaterium e B. subtilis; T7 - A. brasilense + B. licheniformis; T8 - A. brasilense + P. fluorescens; T9 - A. brasilense + B. megaterium e B. subtilis + B. licheniformis; T10 - A. brasilense + B. megaterium e B. subtilis + P. fluorescens; T11 - A. brasilense + B. licheniformis + P. fluorescens; T12 - A. brasilense + B. megaterium e B. subtilis + B. licheniformis + P. fluorescens. In the emission of female inflorescence (R1), plant height, leaf area, dry mass of leaves and dry mass of stem + sheath, relative chlorophyll content, leaf contents of N, P and K were evaluated. At harvest, the levels of N, P and K in the grains, components of production and productivity were determined. Plants inoculated with BPCV showed an increase in height, dry mass of leaves, dry mass of stem + sheath, leaf area and increase in leaf P and K contents in the experiment carried out in Braganey. In the Entre Rios do Oeste experiment, the plants inoculated with BPCV showed an increase in height, leaf dry mass, leaf area and leaf P and K contents. In the two studied places, the inoculated plants showed an increase in the P content in the grains, an increase in the thousandgrain mass and productivity, presenting an increase in the thousand-grain mass from 9% to 27% of and productivity from 11% to 27% in relation to the control without inoculation. The inoculation of A. brasilense, B. licheniformis, B. subtilis, B. megaterium and P. fluorescens, alone or together, promoted greater plant growth and provided greater productivity in the two studied sites.